The Oxford guide to the historical reception of Augustine - Pollmann, Karla; Otten, Willemien (Oxford Univ. Press, 2013)
An international and interdisciplinary enterprise on the impact of Augustine of Hippo. With contributions from over 400 international experts, it offers a detailed introduction and 600 entries which describe, analyse, and evaluate Augustine's influence on a broad variety of key historical figures and themes through the ages.
Erscheinungsjahr in Vorlageform:2013
Keywords: Augustine -- of Hippo, Saint -- 354-430; Augustinus *354-430*; Geistesgeschichte; Geschichte; Aufsatzsammlung; Rezeption; Augustinus, Aurelius <Heiliger>